1993
DOI: 10.2307/1940473
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Demography of Orchids: Intensity and Frequency of Pollination and the Cost of Fruiting

Abstract: Life history theory assumes that there is a trade—off between current reproduction and future growth or reproduction or both; therefore, natural selection is expected to result in the maximization of reproduction within the limits imposed by the trade—off. Accordingly, it has been predicted that fruit and seed production in perennial plants should be resource limited. Many orchid species seem to be pollinator limited, but this hypothesis has been recently challenged by experimental studies that show a cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 37 publications
6
134
1
4
Order By: Relevance
“…A low rate of pollinator visits and fruit production has already been described for other orchid species (Calvo, 1990(Calvo, , 1993. Epidendrum denticulatum shows a low pollination rate and must invest in the defence of its reproductive organs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A low rate of pollinator visits and fruit production has already been described for other orchid species (Calvo, 1990(Calvo, , 1993. Epidendrum denticulatum shows a low pollination rate and must invest in the defence of its reproductive organs.…”
Section: Discussionmentioning
confidence: 76%
“…Various authors agree that many orchid species are infrequently visited by pollinators, with a consequent low fruit set (e.g., Calvo, 1993;Neiland & Wilcock, 1995, 1998. Epidendrum denticulatum Jacq.…”
Section: Introductionmentioning
confidence: 99%
“…Wild orchids have provided important empirical models for studying reproductive costs in iteroparous organisms [28][29][30][31][32][33][34]. Yet how these costs shape observed life histories remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This is most important in long-lived perennials, because increased fecundity may incur costs of reproduction that counteract potential gains. Very few studies have explicitly tied pollination limitation to population trajectories (Bierzychudek 1982, Calvo 1993, Ehrlén and Eriksson 1995, Parker 1997, and these studies present a complicated picture. Ehrlén and Eriksson (1995) found that supplementally pollinated plants of Lathyrus verna increased their seed production by 3.1 times, but then shrank in size, made fewer flowers the next year, and were more likely to enter dormancy than were controls.…”
Section: Putting Pollination Deficits Into the Context Of Plant Life mentioning
confidence: 99%